2023
DOI: 10.1039/d2dt02954e
|View full text |Cite
|
Sign up to set email alerts
|

Pentagonal-bipyramidal 4d and 5d complexes with unquenched orbital angular momentum as a unique platform for advanced single-molecule magnets: current state and perspectives

Abstract: This article overviews the current state and prospects of the concept of advanced single-molecule magnets (SMMs) based on low-spin (S = 1/2) pentagonal-bipyramidal (PBP) 4d3 and 5d3 complexes with unquenched...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 154 publications
(390 reference statements)
0
7
0
Order By: Relevance
“…14,15 Therefore, scientists recently turned their attention to 3d–4f complexes, with the U eff improved by increasing the magnetic couplings between 3d and 4f ions within complexes and utilizing the single-ion anisotropy of 4f ions, especially Dy III . 16–18 Up to now, many 3d-Dy complexes with outstanding SMM performance have been reported. 19–25…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Therefore, scientists recently turned their attention to 3d–4f complexes, with the U eff improved by increasing the magnetic couplings between 3d and 4f ions within complexes and utilizing the single-ion anisotropy of 4f ions, especially Dy III . 16–18 Up to now, many 3d-Dy complexes with outstanding SMM performance have been reported. 19–25…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Therefore, scientists recently turned their attention to 3d-4f complexes, with the U eff improved by increasing the magnetic couplings between 3d and 4f ions within complexes and utilizing the single-ion anisotropy of 4f ions, especially Dy III . [16][17][18] Up to now, many 3d-Dy complexes with outstanding SMM performance have been reported. [19][20][21][22][23][24][25] Among the 3d metal ions, Ni II might be one of the better candidates for constructing SMMs because it often possesses a large single-ion zero-field splitting.…”
Section: Introductionmentioning
confidence: 99%
“…[14] We also noticed that PBPY‐7 complexes of nickel [15] and other metals were scarce [16,17] . Nonetheless, because of the D 5 h symmetry, PBPY‐7 coordination has attracted renewed interest in materials science [18] . Therefore, we envisaged that fundamental studies of a nickel‐PBPY‐7 complexes with ideal D 5 h point symmetry would deepen our understanding of the coordination chemistry of seven‐coordinate metal complexes by providing an interesting and ideal platform for studies of the reactivity and chemical bonding.…”
Section: Introductionmentioning
confidence: 99%
“…[16,17] Nonetheless, because of the D 5h symmetry, PBPY-7 coordination has attracted renewed interest in materials science. [18] Therefore, we envisaged that fundamental studies of a nickel-PBPY-7 complexes with ideal D 5h point symmetry would deepen our understanding of the coordination chemistry of seven-coordinate metal complexes by providing an interesting and ideal platform for studies of the reactivity and chemical bonding. Encouraged by this unique robustness, we started investigating the ligand-and metal-exchange reactions of 1.…”
Section: Introductionmentioning
confidence: 99%
“…Previous theoretical calculations showed that these low-spin orbitally degenerate ( S = 1/2) complexes exhibit highly anisotropic spin coupling with connected spin carriers [ 110 , 111 ]. This is potentially helpful in the development of high-performance SMMs [ 112 , 113 , 114 ]. Incorporation of these molecular synthons into heterometallic coordination compounds has already led to obtaining of SMMs [ 115 , 116 , 117 , 118 , 119 , 120 , 121 ], SCMs [ 122 , 123 , 124 ] and extended polymer structures with unusual magnetic behavior [ 49 , 92 , 125 , 126 , 127 ].…”
Section: Introductionmentioning
confidence: 99%